BSOPM and BOPM Models in Banknifty Options : A Study on Their Applicability and Risk Framework - Rinky; Singh, Shakti; Sachin (Indian Journal of Finance, 2025)
Purpose : In the financial market, frequent changes in RBI’s repo and reverse repo rates influenced the overall securities trading in the stock market’s derivative segment1. The study focused on scrutinizing the applicability of the “BSOPM & BOPM models” to the BANKNIFTY index call and put options on different moneyness scenarios by using three different interest rates. Methodology : This study analyzed 648 samples of BANKNIFTY index call & put options for both models and compared them to assess suitability using risk-free interest rates (MIBOR, 10-year government bond) & risk-including interest rates involving ‘Yield Curve Risk,’ ‘Basis Risk,’ nd ‘Repricing Risk’2. Further, it considered the moneyness of OTM, ATM, and ITM strike prices for each date of the month till expiry and applied SPSS’s paired t-test & RMSE statistical test for analyzing both models. Finding : By analyzing SPSS’s paired t-test, we observed that both models revealed significant differences in option pricing across all levels of moneyness and risk-related variables incorporated into this study, but a comparison of RMSE values identified the BOPM model’s better performance across all computed option prices3. Practical Implications : This research provides useful information for option traders, investors, financial institutions, and policymakers to make more accurate and data-driven financial decisions using option pricing models in different market scenarios. Originality : The study concentrated on considering risk-free and risk-including interest rates at various market scenarios and used a particular one-month option price sample for observations of BSOPM & BOPM for the BANKNIFTY index.